NGF Modulates trkA(NGFR)/p75(NTR) in αSMA-Expressing Conjunctival Fibroblasts from Human Ocular Cicatricial Pemphigoid (OCP) - Micera, Alessandra (PLoS One, 2015)
OBJECTIVE: In a previous study, we reported the upregulation of Nerve Growth Factor (NGF) and trkA(NGFR) expression in Ocular Cicatricial Pemphigoid (OCP), an inflammatory and remodeling eye disease. Herein, we hypothesize a potential NGF-driven mechanism on fibroblasts (FBs) during OCP remodeling events. To verify, human derived OCP-FBs were isolated and characterized either at baseline or after NGF exposure. MATERIALS AND METHODS: Conjunctival biopsies were obtained from 7 patients having OCP and 6 control subjects (cataract surgery). Both conjunctivas and primary FB cultures were characterised for αSMA, NGF and trkA(NGFR)/p75(NTR) expression. Subcultures were exposed to NGF and evaluated for αSMA, NGF, trkA(NGFR)/p75(NTR) expression as well as TGFβ1/IL4 release. For analysis, early and advanced subgroups were defined according to clinical parameters. RESULTS: OCP-conjunctivas showed αSMA-expressing FBs and high NGF levels. Advanced OCP-FBs showed higher αSMA expression associated with higher p75(NTR) and lower trkA(NGFR) expression, as compared to early counterparts. αSMA expression was in keeping with disease severity and correlated to p75(NTR). NGF exposure did not affect trkA(NGFR) levels in early OCP-FBs while decreased both αSMA/p75(NTR) expression and TGFβ1/IL4 release. These effects were not observed in advanced OCP-FBs. CONCLUSIONS: Taken together, these data are suggestive for a NGF/p75(NTR) task in the potential modulation of OCP fibrosis and encourages further studies to fully understand the underlying mechanism occurring in fibrosis. NGF/p75(NTR) might be viewed as a potential therapeutic target.